(untitled) (Research, Society and Development, 2022)
Price is a monetary expression of the value of a product or service. In view of the above, the main objective of this research was to verify how small rural producers of vegetable products from Alta Floresta D’Oeste and Rolim de Moura form their sales prices. It was found that the predominance of the method used is the analysis of competition. A qualitative and quantitative approach was used, employing deductive methods, using a descriptive approach and field study. The data collection techniques were questionnaires for 22 producers, semi-structured interviews for 3 producers and non-participant observation for the sample. The research makes it possible to conclude that the formation of sales prices of products is based on competitors, 59.09% of farmers practice the average price among competitors and that in relation to demand, 63.64% form price according to the season. When asked to classify the variables, customer, competitor and cost as determining factors when pricing their products, the result reveals that the customer comes first in pricing. In relation to what is most important in the pricing process, 31.82% claim to be the profit margin, which is linked to the contribution margin. However, 50% of the owners do not have fixed control over their costs.